Design Thin Film Narrow Band-pass Filters For Dense Wavelength Division Multiplexing - Gaillan H. Abdullah; Bushra R Mhdi; Nahla A.Aljaber (Institute of Advanced Engineering and Science, 2012)
We present tow different design thin film multi-cavity narrow band-pass filter. These filters are most widely used filtration technologies that made possible technical advancement of modern optical communication system. This paper is concerned with a theoretical study on optoelectronics physics to design and analyze this type of filter. A brief introduction to the thin film multi-cavity filter technology will be presented. The recent progress in design thin film multi-cavity technology will be reviewed. These designs consist of two material TiO2 / SiO2 as high / low index. The wavelength range from 600 to 900nm and detecting light at three and four wavelengths' 620,700 and 805 also 625,685,760 and 885nm. The filter is to be coated on Fused Silica having index 1.55 and operates at normal incidence.